Climate Change Mitigation: Role of forest Sector - Gera, Mohit (Indian Forester, 2018)
Paris Agreement, adopted by 197 countries in 2015 reaffirm the goal of limiting the increase in global temperatures to well below 2Â°C compared with pre-industrial levels, with an ambition to limit the increase to 1.5Â°C, necessitating accelerated climate change mitigation measures. The important role of forests in mitigation of climate change is universally recognized. This can broadly be classified into Sequestration, Storage and Substitution. Sequestration involves increasing the removals of CO2 from the atmosphere by activities like afforestation, reforestation, forest restoration, and increasing the tree cover by agro-forestry, farm forestry, urban plantations and similar activities. Storage of carbon is achieved by reducing deforestation and forest degradation, forest conservation and managing the forests for biodiversity and Substitution involves use of wood fuels as a substitute for fossil fuels as well as use of wood in place of carbon intensive materials such as steel and cement concrete. Recognizing the critical role of the forest sector in climate change mitigation, forest management strategies need to be realigned to maximize carbon sequestration, storage and substitution. This strategy also provides substantial co-benefits in the form of livelihood opportunities and numerous goods and services from forests.